The “I” in interaction: authorial presense in academic writing - Monica Chavez Munoz (Revista de Lingüística y Lenguas Aplicadas)
This study explores the discourse functions of personal pronouns and verb forms referring to writer and reader interaction in a corpus of 60 research articles in the fields of linguistics, psychology and educational research in English and Spanish. Drawing on Tang and John’s (1999) taxonomy I elaborate and refine their categories, and propose I as the Interpreter as a new role in the continuum of writers’ authorial presence.  The analysis reveals that both English and Spanish writers make extensive use of pronominal discourse functions. However, Spanish writers use them more sparingly and prefer different functions when signalling their presence such as pointing to their role as interpreters of data rather than recounters of the research process or originators of an original contribution to the field.